Molecular Characterization Reveals the Involvement of Calcium Dependent Protein Kinases in Abiotic Stress Signaling and Development in Chickpea (Cicer arietinum) - Deepika, Deepika; Poddar, Nikita; Kumar, Shailesh; Singh, Amarjeet (Frontiers in Plant Science, 2022)
Calcium dependent protein kinases (CDPKs) are a major group Ca2+ sensors in plants. CDPKs play a dual function of “Ca2+ sensor and responder”. These sensors decode the “Ca2+ signatures” generated in response to adverse growth conditions, such as drought, salinity and cold and developmental processes. However, knowledge of CDPK family in legume crop chickpea is missing. Here, we have identified a total of 22 CDPK genes in the chickpea genome. Phylogenetic analysis of chickpea CDPK family with other plants revealed their evolutionary conservation. Protein homology modelling described the three-dimensional structure of chickpea CDPKs. A defined arrangements of α-helix, β-strands and transmembrane-helix represent important structures like kinase domain, inhibitory junction domain, N and C-lobes of EF hand motifs. Subcellular localization analysis revealed that CaCDPK proteins are localized mainly at the cytoplasm and in the nucleus. Most of the CaCDPK promoters had abiotic stress and development related cis-regulatory elements, suggesting the functional role of CaCDPKs in abiotic stress and development related signaling. RNA-seq expression analysis indicated the role of CaCDPK family in various developmental stages, including vegetative, reproductive development, senescence stages, and during seed stages of early embryogenesis, late embryogenesis, mid and late seed maturity. The qRT-PCR analysis revealed that several CaCDPK genes are specifically as well as commonly induced by drought, salt and ABA. Overall, these findings indicate that the CDPK family is probably involved in abiotic stress responses and development in chickpea. This study provides crucial information of CDPK family that will be utilized in generating abiotic stress tolerant and high yielding chickpea varieties.